Penerapan Rest Api Dalam Perancangan Aplikasi Reservasi Perawatan dan Penitipan Hewan Berbasis Android - Fathur Tias Dewantoro; Anita Fira Waluyo (STMIK Budi Darma, 2023)
One of the most important factors in having an animal is the need for animal care, which means that pet owners have to take the time to take care of their animals, from the problem arose an enterprise that provides various kinds of pet needs including animal care and animal care services namely petshop. In carrying out the process of animal care or care customers need to come to the store and ask for the availability of the schedule of care and stock cage so it takes a lot of time. The research is aimed at assisting the processing of animal care and care transactions so that customers can make the transaction and check the availability of services without having to come to the store and create an Android-based app that can reach the entire customer. To facilitate the development of Android applications, the design uses the Dart programming language with the help of the Flutter framework and the Hypertext Preprocessor Programming Language (PHP) with Laravel as a framework to build the REST API web service technology so that Android applications can be integrated with the central database. From the results of analysis and trials, the ease of transaction by customers and pet store owners has been achieved by developing an Android-based pet care reservation application through the implementation of the REST API. Thus, the design of an Android-based pet care and pet booking application has successfully improved the efficiency of the reservation process, providing easier access to pet owner, and enabling pet service providers to manage schedules more effectively. The application has succeeded in meeting the needs of pet owners in caring and caring for their animals, proving the great potential of the use of modern technology in the animal care industry